Effects of Concentration and Heating/Cooling Rate on Rheological Behavior of Sesamum indicum Seed Hydrocolloid - Ali Rafe; Talieh Shadordizadeh; Mohammad Ali Hesarinejad; Jose M. Lorenzo; Ahmed Ali Abd El-Maksoud; Weiwei Cheng; M. R. Mozafari; Tarek Gamal Abedelmaksoud (Foods, 2022)
Hydrocolloids are known as natural hydrophilic biopolymers that can contribute viscosity and gelation in solution, as well as nutritional benefits, thus, they are widely used in the food industry. In our work, hydrocolloid was isolated by aqueous extraction of Sesamum indicum seed at 80 °C and pH 8.0. The chemical composition and functional properties of Sesamum indicum seed hydrocolloid (SISH) were characterized, and the effects of concentration including 1%, 2%, and 3% as well as heating/cooling rate (1, 5, and 10 °C/min) on the rheological behavior of SISH dispersions in aqueous solution were investigated. The viscoelastic properties of SISH dispersions were characterized by small-amplitude oscillatory shear measurement. The resultant SISH consisted of 60.95% carbohydrate and 23.32% protein, and was thus endowed with a relatively high water-holding capacity, solubility, appropriate emulsifying and foaming properties. Rheological results revealed that the aqueous dispersion of SISH exhibited a non-Newtonian shear-thinning flow behavior. The viscoelastic moduli changes were found to be dependent on SISH concentration, temperature, and heating/cooling rate. Increasing SISH concentrations from 1% to 3% promoted the development of stronger cross-link network. The mechanical spectra derived from strain and frequency sweep measurements showed that the storage moduli were always higher than the loss moduli, and the loss tangent was calculated to be above 0.1 and below 1.0. Furthermore, both moduli had slight frequency dependency, and the complex viscosity exhibited an almost linear reduction with the increase of frequency. Therefore, SISH dispersion behaved as a weak gel-like system. The hysteresis of viscoelastic moduli during heating and cooling reduced with decreasing the heating-cooling rates from 10 to 1 °C/min, suggesting that SISH molecules had enough time to develop a stable and thermally irreversible network. Overall, SISH can be regarded as an acceptable hydrocolloid for generating natural food components with intriguing functional and rheological qualities in the formulation of microstructured goods.